Polystyrene internal support type silicon dioxide aerogel and preparation method thereof
By preparing polystyrene-supported silica aerogels, a stable three-dimensional interpenetrating network structure was formed, which solved the problem of easy breakage of the silica aerogel skeleton and improved the strength and light transmittance of the aerogel.
Patent Information
- Application Number
- CN202411390972.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
The existing silica aerogel framework structure is prone to breakage, leading to performance degradation. Existing reinforcement methods suffer from problems such as differences in interface properties or reduction in specific surface area.
By preparing polystyrene-supported silica aerogel, iron ore tailings slag was mixed with sodium hydroxide and calcined to form hydrogel and alcohol gel. Benzoyl peroxide was added to styrene for permeation replacement to form a three-dimensional interpenetrating network structure, which enhanced the strength of the aerogel.
This method improves the strength of aerogels while maintaining a large specific surface area and light transmittance, forming a stable three-dimensional network structure that inhibits crack propagation.
Smart Images

Figure CN119264509A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogels, and in particular to a polystyrene-supported silica aerogel and a preparation method thereof. Background Art
[0002] Silica aerogel is a spatial network structure composed of nanoparticles, which has the characteristics of low density, large specific surface area, ultra-low thermal conductivity, low refractive index and low sound propagation velocity. Therefore, it has broad application prospects in many fields such as heat insulation, sound insulation, catalyst carriers, adsorbents, drug delivery and optical devices.
[0003] The silica aerogel skeleton has a three-dimensional network structure shaped like a pearl necklace. The secondary particles are connected by point contact, with a small contact area and weak bonds between the particles. As a result, when subjected to external forces, the neck area between the secondary particles is easily broken, causing the connection between the particles to be disconnected, the gel skeleton to collapse, and the aerogel to lose its excellent performance.
[0004] At present, the main methods to enhance the strength of the silica aerogel skeleton structure include the Ostwald ripening process of sol-gel, the introduction of reinforcing phase to prepare composite materials, and increasing the degree of cross-linking of aerogel particles.
[0005] The Ostwald ripening method can strengthen the gel nanonetwork skeleton and improve the strength of the gel, but it will cause problems such as reduced specific surface area, increased pore size, increased density and poor light transmittance.
[0006] The introduction of reinforcing phases (such as fibers, whiskers, particles, etc.) to prepare composite materials using composite process technology, the reinforcing phase as a mechanical support, disperses the external energy on the silica aerogel matrix skeleton, and has the function of conducting and consuming energy for external stress, thereby blocking the expansion of cracks, which can significantly improve the mechanical properties of silica aerogel composite materials and significantly improve the strength of silica aerogel. However, there are obvious differences in the properties of the interface between the two phases, which makes it difficult for the reinforcing phase to be evenly dispersed in the composite material, affecting the comprehensive performance of the composite material.
[0007] Improving the strength of the silica aerogel itself can also improve the strength of the product. For example, introducing cross-linking strengthening phases such as polymers and silanes to improve the connection between aerogel particles and strengthen the cross-linking degree of the aerogel network, strengthening the nano-network skeleton structure of the aerogel matrix material itself, thereby improving the strength of the silica aerogel matrix. This is also the main research and development direction in recent years, and on this basis, new aerogels with novel structures have been developed. Summary of the invention
[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a polystyrene-supported silica aerogel and a preparation method thereof.
[0009] A method for preparing a polystyrene-supported silica aerogel comprises the following steps:
[0010] S1. Mix the iron ore tailings and sodium hydroxide and grind them evenly, calcine at 500-700°C for 1-5h, and grind them after cooling to obtain alkali-burned material;
[0011] S2, adding water to the alkali-burned material and stirring, separating and obtaining a supernatant; adjusting the pH value of the supernatant to 8-11, standing and aging for 1-3 days to obtain a hydrogel;
[0012] S3, washing and replacing the hydrogel with anhydrous ethanol to obtain an alcohol gel;
[0013] S4, adding styrene containing benzoyl peroxide to the alcohol gel for washing, permeation and displacement to obtain a styrene gel;
[0014] S5. Place the styrene gel in an environment of 25-35°C for 30-60 days and vacuum dry it.
[0015] Preferably, in S1, the mass ratio of iron ore tailings to sodium hydroxide is 1:1-3.
[0016] Preferably, in S2, the mass ratio of the alkali-burned material to water is 1:1-5.
[0017] Preferably, in S2, separation is performed by centrifugation at a speed of 3000-10000 rpm.
[0018] Preferably, in S2, the pH value of the supernatant is adjusted to 8-11 using hydrochloric acid with a mass fraction of 4-6%.
[0019] Preferably, in S3, the number of washing and replacement is 3-5 times, each washing time is at least 3 hours, and the volume ratio of anhydrous ethanol used in each washing to the material to be washed is 1-3:1.
[0020] Preferably, in S4, styrene containing benzoyl peroxide is prepared by the following steps: styrene is washed 1-3 times with a sodium hydroxide aqueous solution having a mass fraction of 1-5%, and benzoyl peroxide is added to the washed styrene, wherein the mass ratio of benzoyl peroxide to styrene is 1-5:100.
[0021] Preferably, in S4, the number of washing, permeation and displacement is 3-5 times, and the volume ratio of styrene containing benzoyl peroxide to the material to be washed used in each washing is 1-3:1.
[0022] Preferably, in S5, the vacuum drying temperature is 45-50° C., and the vacuum drying time is 2-4 h.
[0023] A polystyrene-supported silica aerogel is prepared by adopting the preparation method of the polystyrene-supported silica aerogel.
[0024] Beneficial effects:
[0025] The present invention sequentially prepares silica hydrogel and silica alcohol gel, and then replaces ethanol in the silica alcohol gel with styrene, so that styrene is evenly distributed in the gaps of the silica gel, and then is placed in an environment of 25-35°C for thermal polymerization, so that a polystyrene network structure and an original silica network structure form a three-dimensional interpenetrating network structure, the two serve as each other's skeletons, disperse the external energy on their respective skeletons, and have the functions of conducting and consuming energy for external stress, so as to block the expansion of cracks, thereby improving the strength of the obtained silica aerogel, and at the same time, different reaction times can be controlled to obtain polystyrene internally supported silica aerogels with different molecular weights.
[0026] The method of the invention is ingenious, has simple reaction and mild conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the XRD spectrum of the alkali-burned materials obtained in Example 1, Example 5 and Example 6; wherein 5001 is the XRD spectrum of the alkali-burned material obtained in Example 1, 5002 is the XRD spectrum of the alkali-burned material obtained in Example 5, 5003 is the XRD spectrum of the alkali-burned material obtained in Example 6, and 16-0818 and 36-0112 are Na 2 SiO 3 and Na 4 SiO 4 Standard card.
[0028] Figure 2 These are photos of the hydrogel, alcohol gel, styrene gel, and polystyrene-supported silica aerogel obtained in Example 6; wherein a is a photo of the hydrogel, b is a photo of the alcohol gel, c is a photo of the styrene gel, and d is a photo of the polystyrene-supported silica aerogel. DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] The composition of the iron ore tailings used below is shown in Table 1:
[0031] Table 1 Composition of iron ore tailings
[0032]
[0033]
[0034] Example 1
[0035] A method for preparing a polystyrene-supported silica aerogel comprises the following steps:
[0036] S1. Mix the iron ore tailings and sodium hydroxide in a mass ratio of 1:1 and grind them evenly, place them in a muffle furnace and calcine them at 500° C. for 3 h, and grind them into powder after natural cooling to obtain alkali-burned materials;
[0037] S2, adding water to the alkali-burned material and stirring for 3 minutes, the mass ratio of the alkali-burned material to water is 1:1, centrifuging at 3000rpm, washing the centrifugal precipitate twice, and combining the supernatant; continuously stirring the supernatant, adding 4% hydrochloric acid by mass fraction during stirring to adjust the pH value of the system to 8-11, standing and aging for 1 day to form a gel, washing with 1 times (volume) deionized water, washing 3 times to remove impurities such as sodium chloride, and obtaining a hydrogel;
[0038] S3, washing the hydrogel with 1 times (volume) anhydrous ethanol for 3 hours, washing 3 times to obtain an alcohol gel;
[0039] S4, washing the styrene once with a 1% by mass sodium hydroxide aqueous solution to remove the polymerization inhibitor therein, and then adding benzoyl peroxide to the washed styrene (the mass ratio of benzoyl peroxide to styrene is 1:100) to obtain styrene containing benzoyl peroxide;
[0040] The alcohol gel was washed and permeated by using styrene containing 1 volume of benzoyl peroxide for 3 times to obtain a styrene gel;
[0041] S5. Place the styrene gel in a 25°C environment for 30 days and then dry it in a vacuum oven at 45°C for 2 hours.
[0042] Example 2
[0043] A method for preparing a polystyrene-supported silica aerogel comprises the following steps:
[0044] S1. Mix the iron ore tailings and sodium hydroxide in a mass ratio of 1:3 and grind them evenly, place them in a muffle furnace and calcine them at 600° C. for 5 h, and grind them into powder after natural cooling to obtain alkali-burned materials;
[0045] S2, add water to the alkali-burned material and stir for 5 minutes, the mass ratio of the alkali-burned material to water is 1:5, centrifuge at 10000rpm, wash the centrifugal precipitate 4 times, and combine the supernatant; continue to stir the supernatant, add 6% hydrochloric acid by mass during stirring to adjust the pH value of the system to 8-11, let it stand for 3 days to form a gel, wash it with 3 times (volume) deionized water, wash it 5 times to remove impurities such as sodium chloride, and obtain a hydrogel;
[0046] S3, washing the hydrogel with 3 times (volume) anhydrous ethanol for 5 hours, washing 5 times to obtain alcohol gel;
[0047] S4, washing styrene three times with a 5% by mass sodium hydroxide aqueous solution to remove the polymerization inhibitor therein, and then adding benzoyl peroxide to the washed styrene (the mass ratio of benzoyl peroxide to styrene is 5:100) to obtain styrene containing benzoyl peroxide;
[0048] The alcohol gel was washed and permeated by using styrene containing 3 times (volume) of benzoyl peroxide, and washed 5 times to obtain a styrene gel;
[0049] S5. Place the styrene gel in a 35°C environment for 60 days and then dry it in a vacuum oven at 50°C for 4 hours.
[0050] Example 3
[0051] A method for preparing a polystyrene-supported silica aerogel comprises the following steps:
[0052] S1. Mix the iron ore tailings and sodium hydroxide in a mass ratio of 1:1.5 and grind them evenly, place them in a muffle furnace and calcine them at 650°C for 2h, and grind them into powder after natural cooling to obtain alkali-burned materials;
[0053] S2, adding water to the alkali-burned material and stirring for 4.5 minutes, the mass ratio of the alkali-burned material to water is 1:2, centrifuging at 8000rpm, washing the centrifugal precipitate 3 times, and combining the supernatant; continuously stirring the supernatant, adding 4.5% hydrochloric acid by mass fraction during stirring to adjust the pH value of the system to 8-11, standing and aging for 2 days to form a gel, washing with 2.5 times (volume) deionized water, washing 4 times to remove impurities such as sodium chloride, and obtaining a hydrogel;
[0054] S3, washing the hydrogel with 1.5 times (volume) anhydrous ethanol for 4.5 hours, washing 4 times to obtain an alcohol gel;
[0055] S4, washing styrene twice with a 2% by mass sodium hydroxide aqueous solution to remove the polymerization inhibitor therein, and then adding benzoyl peroxide (the mass ratio of benzoyl peroxide to styrene is 4:100) to the washed styrene to obtain styrene containing benzoyl peroxide;
[0056] The alcohol gel was washed and permeated by using styrene containing 1.5 times (volume) of benzoyl peroxide, and washed 4 times to obtain a styrene gel;
[0057] S5. Place the styrene gel in a 32°C environment for 40 days and then dry it in a vacuum oven at 48°C for 2.5 hours.
[0058] Example 4
[0059] A method for preparing a polystyrene-supported silica aerogel comprises the following steps:
[0060] S1. Mix the iron ore tailings and sodium hydroxide in a mass ratio of 1:2.5 and grind them evenly, place them in a muffle furnace and calcine them at 550°C for 4 hours, and grind them into powder after natural cooling to obtain alkali-burned materials;
[0061] S2, add water to the alkali-burned material and stir for 3.5 minutes, the mass ratio of the alkali-burned material to water is 1:4, centrifuge at 4000rpm, wash the centrifugal precipitate 3 times, and combine the supernatant; continue to stir the supernatant, add 5.5% hydrochloric acid by mass fraction during stirring to adjust the pH value of the system to 8-11, let it stand for 2 days to form a gel, wash it with 1.5 times (volume) deionized water, wash it 4 times to remove impurities such as sodium chloride, and obtain a hydrogel;
[0062] S3, washing the hydrogel with 2.5 times (volume) anhydrous ethanol for 3.5 hours, washing 4 times to obtain an alcohol gel;
[0063] S4, washing styrene twice with a 4% by mass sodium hydroxide aqueous solution to remove the polymerization inhibitor therein, and then adding benzoyl peroxide to the washed styrene (the mass ratio of benzoyl peroxide to styrene is 2:100) to obtain styrene containing benzoyl peroxide;
[0064] The alcohol gel was washed and permeated by using styrene containing 2.5 times (volume) of benzoyl peroxide, and washed 4 times to obtain a styrene gel;
[0065] S5. Place the styrene gel in a 28°C environment for 50 days and then dry it in a vacuum oven at 46°C for 3.5 hours.
[0066] Example 5
[0067] A method for preparing a polystyrene-supported silica aerogel comprises the following steps:
[0068] S1. Mix the iron ore tailings and sodium hydroxide in a mass ratio of 1:2 and grind them evenly, place them in a muffle furnace and calcine them at 500°C for 3 hours, and grind them into powder after natural cooling to obtain alkali-burned materials;
[0069] S2, adding water to the alkali-burned material and stirring for 4 minutes, the mass ratio of the alkali-burned material to water is 1:3, centrifuging at 6000rpm, washing the centrifugal precipitate 3 times, and combining the supernatant; continuously stirring the supernatant, adding 5% hydrochloric acid by mass fraction during stirring to adjust the pH value of the system to 8-11, standing and aging for 2 days to form a gel, washing with 2 times (volume) deionized water, washing 4 times to remove impurities such as sodium chloride, and obtaining a hydrogel;
[0070] S3, washing the hydrogel with 2 times (volume) anhydrous ethanol for 4 hours, washing 4 times to obtain alcohol gel;
[0071] S4, washing styrene twice with a 3% by mass sodium hydroxide aqueous solution to remove the polymerization inhibitor therein, and then adding benzoyl peroxide to the washed styrene (the mass ratio of benzoyl peroxide to styrene is 3:100) to obtain styrene containing benzoyl peroxide;
[0072] The alcohol gel was washed and permeated by using styrene containing 2 times (volume) of benzoyl peroxide, and washed 4 times to obtain styrene gel;
[0073] S5. Place the styrene gel in a 30°C environment for 45 days and then dry it in a vacuum oven at 47°C for 3 hours.
[0074] Example 6
[0075] A method for preparing a polystyrene-supported silica aerogel comprises the following steps:
[0076] 10 g of iron ore tailings and 30 g of sodium hydroxide were ground and mixed evenly, put into a muffle furnace, calcined at 500° C. for 3 h, cooled naturally to room temperature, and ground into powder (i.e., alkali-calcined material).
[0077] Take 0.4g of the calcined powder, add 8mL of deionized water, stir and wash thoroughly, transfer to a 10mL centrifuge tube and centrifuge for 2min at 8000r / min to obtain a primary supernatant, which is colorless or light yellow. The separated solid residue is fully washed with 4mL of deionized water and centrifuged under the same conditions to obtain a secondary supernatant. Slowly add the secondary supernatant to the primary supernatant under stirring, and then slowly add 5% hydrochloric acid by mass to adjust the pH value of the supernatant to 10. Stop stirring, let it stand for 3 days to form a hydrogel.
[0078] Add more than 3 times the volume of deionized water to the hydrogel for thorough washing, change the water every 2 hours and wash again, repeat 5 times to completely wash away the sodium chloride in the gel. After washing with water, add more than 3 times the volume of anhydrous ethanol for thorough washing and replacement, wash for more than 3 hours each time, repeat 5 times, and the alcohol gel can be obtained.
[0079] Take 50 mL of styrene, add 50 mL of 5% sodium hydroxide solution, stir and wash twice to obtain pure styrene without inhibitor. Add 1% benzoyl peroxide by mass to the pure styrene and stir evenly. Then add styrene containing initiator at 3 times the volume of alcohol gel to fully wash and replace, repeat 5 times, and you can get styrene gel.
[0080] The styrene gel was sealed and placed in an environment of 30° C. for 30 days for thermal polymerization reaction, and then dried at 50° C. for 3 hours to obtain a polystyrene-supported silica aerogel.
[0081] X-ray diffraction was performed on the alkali-calcined materials obtained in Example 1, Example 5 and Example 6. Figure 1 As shown, 5001 is the XRD spectrum of the alkali-burned material obtained in Example 1, 5002 is the XRD spectrum of the alkali-burned material obtained in Example 5, 5003 is the XRD spectrum of the alkali-burned material obtained in Example 6, and 16-0818 and 36-0112 are respectively Na 2 SiO 3 and Na 4 SiO 4 Standard card.
[0082] like Figure 1 As shown in the figure, when the mass ratio of iron ore tailings and sodium hydroxide changes from 1:1 to 1:3, the product changes from Na 2 SiO 3 Gradually transforming into Na 4 SiO 4 When the mass is relatively high, there is obvious unreacted SiO 2 The diffraction peak comes from the iron ore tailings, as shown by ◆ on 5001 in the figure. Therefore, when treating the iron ore tailings, it is preferred to calcine them at a mass ratio of 1:3.
[0083] The photos of the hydrogel, alcohol gel, styrene gel and polystyrene-supported silica aerogel obtained in Example 6 are as follows Figure 2 As shown, the first three are fluffy colloidal substances, which are easy to collapse and form white carbon black after drying, while polystyrene has a certain shape and strength and is transparent. It can still maintain its original structure after drying, that is, polystyrene internal support silica aerogel is obtained.
[0084] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing polystyrene-supported silica aerogel, characterized in that: The steps include: S1. Mix the iron ore tailings and sodium hydroxide and grind them evenly, calcine them at 500-700°C for 1-5h, and grind them after cooling to obtain alkali-burned materials; S2, adding water to the alkali-burned material and stirring, separating and obtaining a supernatant; adjusting the pH value of the supernatant to 8-11, standing and aging for 1-3 days to obtain a hydrogel; S3, washing and replacing the hydrogel with anhydrous ethanol to obtain an alcohol gel; S4, adding styrene containing benzoyl peroxide to the alcohol gel for washing, permeation and displacement to obtain a styrene gel; S5. Place the styrene gel in an environment of 25-35°C for 30-60 days and vacuum dry it.
2. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S1, the mass ratio of iron ore tailings to sodium hydroxide is 1:1-3.
3. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S2, the mass ratio of alkali-burned material to water is 1:1-5.
4. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S2, separation is performed by centrifugation, and the centrifugal speed is 3000-10000 rpm.
5. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S2, the pH value of the supernatant is adjusted to 8-11 using hydrochloric acid with a mass fraction of 4-6%.
6. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S3, the number of washing and replacement is 3-5 times, each washing time is at least 3 hours, and the volume ratio of anhydrous ethanol used in each washing to the material to be washed is 1-3:
1.
7. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S4, styrene containing benzoyl peroxide is prepared by the following steps: styrene is washed 1-3 times with a sodium hydroxide aqueous solution with a mass fraction of 1-5%, and benzoyl peroxide is added to the washed styrene, and the mass ratio of benzoyl peroxide to styrene is 1-5:
100.
8. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S4, the number of washing, penetration and displacement is 3-5 times, and the volume ratio of styrene containing benzoyl peroxide to the material to be washed in each washing is 1-3:
1.
9. The method for preparing the polystyrene-supported silica aerogel according to claim 1, characterized in that: In S5, the vacuum drying temperature is 45-50° C., and the vacuum drying time is 2-4 h.
10. A polystyrene-supported silica aerogel, characterized in that: The aerogel is prepared by the method for preparing the polystyrene-supported silica aerogel according to any one of claims 1 to 9.